High User Satisfaction Rates with DEXCOM™ Continuous Glucose Monitoring Device in People with Type 1 Diabetes—A Pilot Cross-Sectional Study - Benái Paponette; Laura Keaver; Peter Lynch; Elias Eltoum; Liam Clarke; Jordan Carty; Siobhan Bacon; Catherine McHugh (Diabetology, 2025)
Background/Objectives: DEXCOM™ continuous glucose monitoring devices (DCGMs) have been shown to improve glycaemic control and complication rates in people with Type 1 diabetes (T1DM). However, little qualitative data exists regarding user satisfaction, useful features and the overall lived experience of using a DCGM which will strongly impact one’s quality of life (QOL), compliance and the self-management of diabetes. This study aimed to assess DCGM users’ satisfaction rates and experiences with device features in patients with T1DM in Ireland. Methods: A questionnaire consisting of open- and closed-ended questions together with a glucose monitoring satisfaction survey (GMSS) was offered to all patients attending Sligo University Hospital (SUH) diabetes clinic who used a DCGM for at least six months. Results: Data was analysed for 73 participants. Self-reported QOL improved in 88% of participants and 52% of participants reported fewer hypoglycaemic events. The features most liked by participants were alerts given when the glycaemic target was not in range, improved quality of life, improved hypoglycaemia awareness and the need for reduced finger pricking. However, concerns were also identified about redundant alarms and sensor failures, phone incompatibility and skin reactions. DCGM was associated with good levels of glucose monitoring satisfaction with an overall satisfaction score of 3.67 ± 1.24 out of 5. Participants reported high openness (4.01 ± 0.91), increased trust (3.77 ± 1.16) and low emotional (1.70 ± 0.97) and behavioural burden (2.38 ± 1.10) with DCGM usage. Male participants who had diabetes for a mean duration of 20.06 ± 0.89 years and used DEXCOMTM for approximately 2 years demonstrated significantly higher levels of satisfaction (p < 0.05). Conclusions: The findings of this study provide a first exploration of patients’ perspectives on DCGM devices in an Irish setting. Results suggest that DCGM users are highly satisfied with the device with an increase in self-reported QOL. Adaptations to features based on patient feedback should be considered to further enhance user satisfaction and maximise QOL benefits.